As Missões Jesuítico-Guaranis e as políticas de preservação do patrimônio histórico-cultural no Mercosul: da nação à integração? - de Loyola, Erico Teixeira; Mario Kerber, Alessander (Museologia e Patrimônio, 2016)
The present paper intends to discuss some of the initiatives that took place within the Mercosur to foster the preservation of the Jesuit Missions of the Guaranis, and, therefore, to increment cultural integration, in contrast with the national narratives developed by Brazilian, Argentinean and Paraguayan official heritage institutions in the 1930s-1940s towards these ruins. To this end, this paper, based on the existent bibliography on the matter, presents and analyses the original "nationalizing" narratives developed by such official heritage institutions in what regards the Jesuit Missions of the Guaranis, and how they differ from the mentioned Mercosur initiatives, in which the national aspect is apparently overlapped by an integration speech. Thus, this work concludes that though the Mercosur state-members are still leading role the processes of "heritage activation" (PRATS, 1997), the narratives consolidated within the bloc cultural instances of bloc are potentially different from those originally imagined when such official preservation bodies were established, with greater emphasis on the international character of the Missions, in order to strengthen the cultural ties between those Member-States.